Maximizing Charitable Endowments for Healthcare: Maqasid Shariah Perspectives from Wahbah Zuhaili and Shariah Economic Laws Compilation - Anwar, Maulana; Afif Noor (Dinasti Research, 2024)
A gift is a voluntary agreement without compensation, either to heirs or other people. However, its implementation will have an impact on conflict when the grantor suffers from illness. Of course, this has different legal implications than for healthy people. This study focuses on the opinions of Wahbah Al-Zuhaili and KHES. This research method uses library research, which is qualitatively analytical through a historical approach and a statute approach. The data analysis method uses the fiqh muqaran approach. The results of the research show that first, the law of giving sick people maqasid Shariah values is found in the following aspects: protecting religion, protecting the soul, protecting the mind, protecting property, and protecting offspring. Second, Wahbah al-Zuhaili classified illness conditions as serious illness and non-severe illness. Conditions of serious illness that cause death before one year has passed, the law applies to people who are seriously ill and cause death. Meanwhile, for illnesses that are not serious or do not cause death, the grantor may commit with the recipient to pay for life until death, as stated in Article 454 paragraph 2. Third, KHES specifically includes grants for seriously ill people in articles 724–727.